If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying m + -1 = -2 + -9 Reorder the terms: -1 + m = -2 + -9 Combine like terms: -2 + -9 = -11 -1 + m = -11 Solving -1 + m = -11 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + m = -11 + 1 Combine like terms: -1 + 1 = 0 0 + m = -11 + 1 m = -11 + 1 Combine like terms: -11 + 1 = -10 m = -10 Simplifying m = -10
| 5w^2-23w-42=0 | | s=L-rL | | 2x-36=5(x+3) | | 100=20t+5t^2 | | 4-5X=59 | | 4x-3x=1x | | 6a^2-5a-4=0 | | 5x=6x+31 | | 25.00x=4.50 | | 3y-2+6x=0 | | 2x-6=3x+1-x-2 | | 4x^2+4x=9 | | 2(x+4)-5=2x+13 | | n+5=9+2n-3-8 | | .5(4x-10)=52+3x | | 69=3v | | 3x-6+x+8=42 | | 5xy^2+3xy^2= | | -5w^2+23w-42=0 | | 11=4x-3y | | 0=-16t^2+50t+6 | | 5x-4=3x+2x+3-2+1 | | 72=5c+7c-2c | | n+5=-1-16 | | 2(-3a+5)=2y+3 | | 68=4v | | a(a^7+1)-7(a^7+1)=0 | | 4x-3=x-3+3x | | 3(4)-6+4+8=42 | | m+5=1 | | 12x-7=27x+3 | | -1x=13 |